2002
DOI: 10.1002/ar.10101
|View full text |Cite
|
Sign up to set email alerts
|

Conduction system abnormalities in rat embryos induced by maternal hyperthermia

Abstract: Maternal hyperthermia induces severe malformations in the central nervous system (CNS) in both humans and laboratory animals. These phenomena are accompanied by apoptotic cell death, especially in the developing CNS. Cardiovascular malformations in conjunction with skeletal and CNS abnormalities have been reported in embryos of laboratory animals. In rats, hyperthermic treatment at 43°C for 15 min at day 9 of pregnancy induced various severe external malformations in embryos, such as exencephaly, spina bifida,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…One possible explanation for the sensitivity of cells in the conduction pathway to corticosteroid exposure is that like neurons, Purkinje fibers are susceptible to cellular stress. Studies in rat embryos showed that maternal hyperthermia caused malformations in both the central nervous system and cardiac conduction system (6). Although Purkinje fiber development has not been as thoroughly studied in the ovine fetus in terms of factors inducing Purkinje fiber maturation, structural studies of the ovine heart show that the time of our treatment corresponds to the end of the development of a fibrous sheath around the septal Purkinje fibers and the beginning of the ensheathment of the ventricular Purkinje fibers; formation of this sheath is complete, well organized, and dense by gestational day 140, but nonexistent at day 115 (12).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the sensitivity of cells in the conduction pathway to corticosteroid exposure is that like neurons, Purkinje fibers are susceptible to cellular stress. Studies in rat embryos showed that maternal hyperthermia caused malformations in both the central nervous system and cardiac conduction system (6). Although Purkinje fiber development has not been as thoroughly studied in the ovine fetus in terms of factors inducing Purkinje fiber maturation, structural studies of the ovine heart show that the time of our treatment corresponds to the end of the development of a fibrous sheath around the septal Purkinje fibers and the beginning of the ensheathment of the ventricular Purkinje fibers; formation of this sheath is complete, well organized, and dense by gestational day 140, but nonexistent at day 115 (12).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our model of Zn deficiency, we show reduced HNK-1 expression in the heart, in regions that are in close proximity of certain components of the CCS (namely, the SAN and AVN). The interpretation of these results is challenging as HNK-1 has been used to probe both the NCC and the components of the CCS [53][54][55][56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we assessed Cx43 expression as an indicator of cardiac NCC populating the heart, whereas SMA staining was used to trace the abundance of NCC-derived smooth muscle cells [50][51][52]. We also determined the changes in HNK-1 staining distribution and intensity, as this sulfated carbohydrate epitope is also expressed by NCC; however, in the rats, HNK-1 has also been used as a probe for the components of the cardiac conduction system (CCS) as well [53][54][55][56][57][58][59][60][61]. Finally, because they potentially may be influenced by Zn status, we monitored the expression of GATA-4 and FOG-2, two Zn-finger transcription factors that regulate the expression of a variety of structural and regulatory genes, critical for cardiac morphogenesis [62][63][64], but are not associated with cardiac NCC patterning and function.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last century, most of the studies investigating the teratogenic effects of increased maternal body temperature have reported a preponderance of central nervous system (CNS) defects, suggesting that the CNS is more susceptible than other organ systems Jessop, 1959, 1963;Hakosalo and Saxen, 1971;Miller et al, 1978;Layde et al, 1980;Shiota, 1982;Milunsky et al, 1992;Zhang and Cai, 1993;Suarez et al, 2004;Li et al, 2007;). Indeed, other malformations such as oral clefts, micropthalmia, cerebral palsy, and talipes equinovarus (clubfoot) have been reported infrequently (Edwards, 1971;Smith et al, 1978;Hendrickx et al, 1979;Pleet et al, 1981;Shiota, 1982;Nilsen, 1984;Germain et al, 1985;Aoyama et al, 2002). Because the teratogenic effects of increased body temperatures are probably not limited to a specific birth defect, infants exposed in utero to a hyperthermic environment might have more than one birth defect, depending on the gestational period as well as duration and intensity of the hyperthermic exposure (Edwards, 2006).…”
Section: Maternal Fever and Oral Cleftsmentioning
confidence: 99%